2012
DOI: 10.5194/tc-6-771-2012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of basal conditions in an inverse model: Vestfonna ice cap, Nordaustlandet/Svalbard

Abstract: Abstract. The dynamics of Vestfonna ice cap (Svalbard) are dominated by fast-flowing outlet glaciers. Its mass balance is poorly known and affected dynamically by these fast-flowing outlet glaciers. Hence, it is a challenging target for ice flow modeling. Precise knowledge of the basal conditions and implementation of a good sliding law are crucial for the modeling of this ice cap. Here we use the full-Stokes finite element code Elmer/Ice to model the 3-D flow over the whole ice cap. We use a Robin inverse met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 49 publications
3
51
3
Order By: Relevance
“…As for glaciological applications, velocities and strain rates can vary by several orders of magnitude inside the domain, and we have observed that including the nodal weights in the definition of the Fréchet derivatives leads to good convergence properties when using an unstructured mesh where large elements correspond to low-velocity areas, and vice versa. Possible alternatives are, for the control inverse method (Morlighem et al, 2010), to use a cost function that measures the logarithm of the misfit or, for the Robin inverse method (Arthern and Gudmundsson, 2010), to use a spatially varying step size rather than a fixed step in the gradient descent algorithm, as proposed in Schäfer et al (2012).…”
Section: Minimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…As for glaciological applications, velocities and strain rates can vary by several orders of magnitude inside the domain, and we have observed that including the nodal weights in the definition of the Fréchet derivatives leads to good convergence properties when using an unstructured mesh where large elements correspond to low-velocity areas, and vice versa. Possible alternatives are, for the control inverse method (Morlighem et al, 2010), to use a cost function that measures the logarithm of the misfit or, for the Robin inverse method (Arthern and Gudmundsson, 2010), to use a spatially varying step size rather than a fixed step in the gradient descent algorithm, as proposed in Schäfer et al (2012).…”
Section: Minimisationmentioning
confidence: 99%
“…Elmer/Ice was further used as a reference for the later MISMIP3d experiments (Pattyn et al, 2013). Recently, data assimilation was implemented within Elmer/Ice (Jay-Allemand et al, 2011;Schäfer et al, 2012;Gillet-Chaulet et al, 2012) to infer poorly known parameters such as basal drag. Today, Elmer/Ice is the only three-dimensional full-Stokes model that solves the grounding line dynamics (Favier et al, 2012), and it will be the only full-Stokes model able to run forecast simulations for the whole Greenland ice sheet for the coming AR5 IPPC report, in the framework of both SeaRISE and ice2sea Shannon et al, 2013;Edwards et al, 2013) programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The research area and observational data have been presented in detail by Schäfer et al (2012). Key features and additional data are described in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been implemented and applied with success in ice flow models of different complexity in order to infer the basal drag, one of the most uncertain model parameters (e.g. Morlighem et al, 2010;Jay-Allemand et al, 2011;Schäfer et al, 2012;GilletChaulet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%